Role of Physical Literacy in Quality of Life: Mediating Activity and Resilience - Siti Rukmiyanti; Muchamad Ishak; Andy Supriady (Universitas Negeri Semarang, 2026)
This study investigates how physical literacy affects students' quality of life while studying physical activity and resilience as intermediate factors. The research used a cross-sectional design to study 350 active students from West Bandung Regency who were chosen through random sampling. Data collection for the research study was conducted using four instruments which included the Perceived Physical Literacy Instrument (PPLI) and the International Physical Activity Questionnaire-Short Form (IPAQ-SF) and the Indonesian Resilience Scale and the WHOQOL-BREF. The researchers used PROCESS Macro for SPSS Model 6 to conduct their data analysis which needed bootstrap resampling with 5,000 samples to assess direct and indirect relationships. The findings showed that physical literacy functions as a significant predictor for both physical activity and resilience (p < 0.001) whereas physical activity acts as a significant predictor for resilience (p < 0.001). The study found that physical activity and resilience both improve quality of life while resilience makes the largest positive impact. The study found that physical literacy did not produce a direct impact on quality of life because the results showed no significant relationship (p > 0.05). The study identified significant indirect effects which demonstrated that physical activity and resilience function as complete mediators between physical literacy and quality of life. The research shows that students need to develop physical literacy through physical activity and resilience training because this process will enhance their overall quality of life.